Navigating criminal liability in an era of AI-assisted medicine - Mrčela, Marin (Medicine, law & society, 2025)
This paper explores the interplay between artificial intelligence (AI) and criminal liability within the healthcare sector, particularly in the context of medical malpractice. Adopting a multidisciplinary approach, the study evaluates current legal frameworks and their adequacy in addressing liability for errors involving AI-driven medical systems. Through an analysis of legal theory, case studies, and technological integration, the research highlights the complexities of assigning liability when errors arise from AIassisted medical decision-making. The methodology includes a comparative legal analysis and a detailed examination of a realworld case involving AI-related treatment errors. Findings reveal that while existing legal frameworks are sufficient for holding humans accountable under the standard of care, they struggle with the unique challenges posed by AI's "black-box" nature. The study argues that further refinement of liability models is necessary, especially as AI systems gain greater autonomy. The paper concludes by offering a roadmap for balancing innovation in AI with the imperative to protect patient rights, emphasizing that liability frameworks must evolve in tandem with technological advancements.
Keywords: accountability; AI-assisted medicine; criminal; liability; standard of care